Community Participation in Regional Development Planning: A Literature Review - Priska Septiana Margareta; Salahudin Salahudin (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2021)
This study aimed to examine the understanding of community participation in development planning. The literature review was used and involved reading and reviewing the main ideas to add arguments and opinions on the topic raised. This helped determine the shortcomings of previous studies to improve and make more regular formulations. The results showed that regional development needs to involve the community in planning, implementation, monitoring, and evaluation. This is because community participation is an important aspect in the overall development process. However, the articles presented differ from the conditions in each country. There is a need for understanding of the government system in the articles used as references. Therefore, special considerations for determining similarities and discoveries from the articles used as references are critical and may help develop the main idea based on the topic and the title.